2020
DOI: 10.1002/ddr.21748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sinomenine on the proliferation, cytokine production, and regulatory T‐cell frequency in peripheral blood mononuclear cells of rheumatoid arthritis patients

Abstract: Sinomenine (SN) is a plant‐derived alkaloid isolated from Caulis Sinomenii. It has been approved by the State Food and Drug Administration of China for treating rheumatoid arthritis (RA) nearly 20 years ago. To investigate the anti‐RA mechanism of SN, a lot of scholars reported the immunosuppressive effect of SN on T lymphocytes. We continued to evaluate the suppressive function of SN by using human peripheral blood mononuclear cells (PBMCs) isolated from RA patients. As the positive control, 10 ng/ml of methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…On Day 10, the levels of all cytokines except IFN-g significantly decreased (Figure 3C), concomitant with the improvement of rash. These findings might be attributed to the use of methylprednisolone, as a previous study demonstrated that methylprednisolone could decrease the peripheral cytokine levels (i.e., IL-4, IL-6, IL-10, IL-17, IFN-g, and TNF-a) in patients with rheumatoid arthritis (32). Moreover, it might be possible that IFN-g levels on Day 2 had decreased significantly because during that time, methylprednisolone had already been used for four days.…”
Section: Discussionmentioning
confidence: 84%
“…On Day 10, the levels of all cytokines except IFN-g significantly decreased (Figure 3C), concomitant with the improvement of rash. These findings might be attributed to the use of methylprednisolone, as a previous study demonstrated that methylprednisolone could decrease the peripheral cytokine levels (i.e., IL-4, IL-6, IL-10, IL-17, IFN-g, and TNF-a) in patients with rheumatoid arthritis (32). Moreover, it might be possible that IFN-g levels on Day 2 had decreased significantly because during that time, methylprednisolone had already been used for four days.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, the basic principles of disease treatment are to promote blood circulation, relieve pain, detoxify and dredge collaterals, dispel wind, and remove dampness[ 17 ]. Sinomenine, an alkaloid extracted from Caulis sinomenii , can inhibit bone destruction and inflammatory reactions, relax tendons and activate blood, expel wind, and remove dampness without inducing significant side effects[ 18 ]. Zhengqing Fengtongning injection is a Chinese medicinal preparation extracted from sinomenine.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org (0.3-30 μM) has been defined as having a limited effect on Th cells and Treg cells from mitogen-activated PBMCs isolated from RA patients in vitro (Xu et al, 2021). As previously reported, intraperitoneal injection of sinomenine (20 mg/kg) failed to achieve expected efficacy in CIA rats (Tong et al, 2015).…”
Section: Sinomeninementioning
confidence: 95%
“…In vitro , sinomenine treatment (1 mM) suppressed the proliferation and secretion of TNF-α and IL-17 in PBMCs activated by type II collagen (CII) ( Tong et al, 2015 ). Interestingly, sinomenine (0.3–30 μM) has been defined as having a limited effect on Th cells and Treg cells from mitogen-activated PBMCs isolated from RA patients in vitro ( Xu et al, 2021 ). As previously reported, intraperitoneal injection of sinomenine (20 mg/kg) failed to achieve expected efficacy in CIA rats ( Tong et al, 2015 ).…”
Section: Representative Effective Components Of Tcm Botanical Drugs I...mentioning
confidence: 99%